Torque stability of different abutment screws submitted to mechanical cycling - Vianna, Camila de Assis [UNESP]; Aparecida Delben, Juliana [UNESP]; Barão, Valentim A.R.; Barbosa Ferreira, Mayara [UNESP]; Henrique dos Santos, Paulo [UNESP]; Gonçalves Assunçao, Wirley [UNESP] (Quintessence Publishing, 2013)
Purpose: To evaluate the torque stability of different UCLA retention screws of single implant-supported crowns submitted to mechanical cycling. Materials and Methods: Crowns fabricated from nickel-chromiummolybdenum alloy were attached to external-hexagon implants and grouped by the different retention screws used (n = 10): Ti, titanium screws (BRUNIHT, Biomet 3i); Au, gold-palladium screws with 24-carat gold coating (Gold-Tite, Biomet 3i); TiC, titanium alloy (Ti-6Al-4V) screw with diamondlike carbon coating (Neotorque, Neodent); and TiN, Ti-6Al-4V screw with aluminum-titanium-nitride coating (Ti-Tite, Conexão). Three initial removal torque (RT) values were obtained for each screw after torque insertion using an analog torque gauge. The final RT was measured after mechanical cycling (1 × 106 cycles at 2 Hz under 130 N). Data were submitted to analysis of variance and the Fischer test. Results: Statistically significant differences were observed between the initial RT in groups Ti and TiN, and between TiC and TiN. No statistically significant difference was seen between mean RT obtained before and after mechanical cycling, except for the Ti screws. All groups exhibited similar torque maintenance after mechanical cycling. Conclusion: Although no significant difference was observed among groups for the final percentage of torque maintenance, the final RT values of the coated screws were higher than those of the noncoated screws. © 2013 by Quintessence Publishing Co Inc.
Keywords: Coating; Gold; Implant-supported prosthesis; Retention screw; Titanium; Torque maintenance